Sailing through the storm: Improvising paradox navigation during a pandemic. Issue 1 (February 2023) - Lê, Patrick; Pradies, Camille
Despite rich depictions of paradox navigation strategies, and the recognition that they are fraught with uncertainty, research reveals relatively little about how leaders navigate paradoxical tensions when improvising in the face of highly unpredictable and quickly evolving events. We conducted a narrative study of how French President Macron navigated the tension between the paradoxical poles of "saving lives" and "preserving life as usual" during the pandemic. Our article surfaces three central elements that form a model of improvised paradox navigation in stormy conditions: turning points, fog of uncertainty, and chaotic learning. Our model contributes to paradox theorizing by shedding light on paradox navigation in highly turbulent environments and has implications for management learning and improvisation.